Demographic profile in liver transplant candidates on waiting list - Winckler, Camila César; Biagioni, Daniela Salate; Paula, Regina Célia Callile de; Gomes, Milene Regina Bailo; Llanos, Juan Carlos; Bakonyi Neto, Alexandre; Silva, Giovanni Faria; Almeida, Ricardo Augusto Monteiro de Barros; Polônio, Rodrigo Jose (Brazilian Journal of Transplantation, 2010)
Liver transplantation is a life-saving therapy for patients with end-stage liver diseases. The post-transplant outcome depends on a wide knowledge of the patient’s status and factors that may influence results and complications, as well as an interdisciplinary team approach. The assessment of liver transplant candidates includes both demographic and clinical aspects. Purpose: To assess the liver transplant candidates’ profile in a Brazilian Medical School. Methods: Data from a retrospective analysis were attained from the records of patients included on the waiting list between October, 2003 and January, 2005. Results: Forty-four patients were included on the waiting list, being 90% (n=40) older than 40 years, and 84% male (n=37); white, 84% (n=37); married, 75% (n=33), and catholic, 72.8% (n=32). Patients’ blood typing was A, B, AB, or O in 45.4%, 11.4%, 4.5%, and 38.7% patients, respectively. The occupation profile showed eleven patients in working active status (24.9%), with a lower than U130.00 average monthly income in 18 (40.9%) patients. The most frequent diagnosis was alcoholic cirrhosis (n=19; 43.2%) followed by hepatitis C virus in 9 patients (20.4%). According to the Child-Turcotte-Pugh scores, patients were classified as in B or C (81.8%). Discussion: The high concentration of the sugar cane in that region is probably responsible by the increasing distilled drink intake among patients. The resulting lack of activity of the terminal hepatic disease deprives them to offer support for their families, and the multi professional support is the most important approach to incentive the avoidance of a relapse of the after-transplant alcoholic ingestion. Conclusion: Patients’ profile on our liver transplant waiting list showed poor, white, male, and inactive patients with alcoholic liver disease as the main reason for the transplantation.